'The sickness stands at your shoulder …': Embodiment and cognitive metaphor in Hornbacher's Wasted: A Memoir of Anorexia and Bulimia. (February 2016) - Senkbeil, Karsten; Hoppe, Nicola
This paper applies cognitive linguistic approaches, particularly conceptual metaphor theory, to the study of literature, and analyses how Wasted: A Memoir of Anorexia and Bulimia (1998) by Marya Hornbacher communicates embodied experiences such as sickness, hunger, and (self-)loathing with the help of conceptual metaphors. It explores how the author renegotiates and partly recontextualizes highly conventionalized metaphors around eating disorders, mental illness, and identity to create new meaning, and how this strategy helped explain the mindset of a person with anorexia and bulimia to a broad critical readership in the late 1990s. This paper hence hypothesizes that the book's emphasis on metaphors as a means to articulate bodily experiences surrounding a mental disorder may hint towards larger trends concerning the representation of the body–mind relationship in literature and culture in the last two decades.